THE CYTOTOXIC ACTIVITY OF N-HEXANE EXTRACT OF KERSEN(muntingia calabura linn.) LEAVES USING THE BRINE SHRIMP LETHALITY TEST (BSLT) METHOD - Irma Sari; Titania Miranda; Sadli Sadli (Universitas Syiah Kuala, 2016)
The cytotoxic activity experiment of n-hexane extract of kersen (Muntingia calabura Linn.) leaves has been carried out using the Brine Shrimp Lethality Test (BSLT) method. The purpose of this research is to identify the secondary metabolites, extract characterize, and determine the LC50 value of the extract against larvae shrimp Artemia salina Leach. Screening result showed that n-hexane extract of kersen leaves contain triterpenoid. Extract characterization showed the results water content of 2.59±0.18 %w/w, water soluble extractive content of 1.9%±0.19 %w/w, the ethanol soluble extractive content of 17.41±1,87 %w/w and total ash value 0.25% w/w. Extract showed LC50 value is 278,72 ppm were calculated by probit analysis. The LC50 value indicated that the n-hexane extract of kersen leaves potentially has cytotoxic activity.